Which sustainability dimensions affect credit risk? Evidence from corporate and country-level measures - Lutfi Abdul Razak; Mansor Haji Ibrahim; Adam Ng (Journal of Risk and Financial Management, 2020)
Amid growing concern over sustainability issues, there is increasing demand to incorporate environmental and social issues into assessments of credit risk, the possibility of loss resulting from a borrower's failure to meet their financial obligations. In this paper, we sought to identify empirical evidence of a relationship between sustainability measures and credit risk. We contribute to this literature in three main ways: firstly, by using a measure that considers the financial materiality of sustainability issues across different industries; secondly, by using corporate default swap (CDS) spreads as a market-based measure of credit risk; and thirdly, by exploring the context-dependent nature of the relationship. Though the extent differs across industries, our results suggest risk-reducing effects across several corporate sustainability dimensions: climate change; natural resource use; human capital and corporate governance. Furthermore, we found that country sustainability plays a moderating role in the nexus between corporate sustainability and credit risk. Hence, a one-size-fits-all policy may not be suitable in developing the credit-relevant standardization of sustainability factors. Nevertheless, the robustness of corporate governance throughout our findings suggests that corporations should strengthen governance frameworks and procedures prior to embarking on environmental and social objectives to mitigate credit risk.
Keywords: 330; corporate social performance; environmental; social and governance; corporate financial performance; corporate default swaps; credit risk; country sustainability